IMPLEMENTATION OF AUGMENTED REALITY (AR) PRIMARY SCHOOL STUDENTS SCIENCE LEARNING : A SYSTEMATIC LITERATURE - Hariratul Mahya, Berlian; Ngabianto; Ellianawati; Subali, Bambang; Sholeh, Muh.; Kurniawan, Edi; Joko Raharjo, Tri (PIONIR: JURNAL PENDIDIKAN, 2026)
Primary science education fosters critical, analytical, and reflective thinking, though students frequently struggle with abstract concepts. To address this urgent issue, this study investigates publication trends and the overall efficacy of Augmented Reality (AR) from 2022 to 2025. Following a PRISMA-guided Systematic Literature Review (SLR) approach, the research scope was strictly limited to English peer-reviewed articles indexed in Scopus (Q2–Q3) and SINTA 2. Out of 1,000 records screened from the Google Scholar and Scopus databases, 23 met the inclusion criteria and were thoroughly analyzed using Publish or Perish, Microsoft Excel, and VOSviewer. Results show a publication surge peaking in 2025, with Semarang State University emerging as the top institutional contributor. Bibliometric mapping successfully identified two major research clusters: learning outcome evaluation metrics and advanced technology integration modes. While 3D AR visualizations effectively enhance student engagement and cognitive retention, a deeper synthesis uncovers critical barriers, including hardware gaps, low teacher technological readiness, and a lack of longitudinal studies. The distinct novelty of this study lies in its chronological overview of post-pandemic digital acceleration in elementary education, providing a strategic framework for immersive 21st-century curriculum design. Keywords: Augmented Reality, Learning Outcomes, and Science Education